2004
DOI: 10.3102/00028312041003527
|View full text |Cite
|
Sign up to set email alerts
|

Accountability and Single-Sex Schooling: A Collision of Reform Agendas

Abstract: This ethnographic study documents how accountability measures skewed the implementation of gender equity reform at one California public middle school serving low-income students of color. In creating single-sex classes throughout the school, the Single Sex Academy (SSA) became the largest public experiment with single-sex schooling in the country, but pressure to raise its standardized test scores diverted the school away from the exploration and implementation of the gender reform. The chronicle of SSA is pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…The ambiguous, even contradictory nature of the findings further complicates the discerning of potential benefits of SSI (Haag, 2000;Herr & Arms, 2004;Jackson & Smith, 2000;Mael et al, 2005;Thompson & Ungerleider, 2004). Of the 43 studies reviewed in Mael et al's meta-analysis, the researchers reported that, in terms of academic gains, 35% favored SSI, 2% favored CE instruction, 53% showed no difference, and 10% had mixed results (i.e., results differed by academic subject or sex).…”
Section: Achievement Effects Of Ssimentioning
confidence: 99%
“…The ambiguous, even contradictory nature of the findings further complicates the discerning of potential benefits of SSI (Haag, 2000;Herr & Arms, 2004;Jackson & Smith, 2000;Mael et al, 2005;Thompson & Ungerleider, 2004). Of the 43 studies reviewed in Mael et al's meta-analysis, the researchers reported that, in terms of academic gains, 35% favored SSI, 2% favored CE instruction, 53% showed no difference, and 10% had mixed results (i.e., results differed by academic subject or sex).…”
Section: Achievement Effects Of Ssimentioning
confidence: 99%
“…(GARF A2306/72/446/32) By attributing problems more to structural conditions than to gender-separated schooling, this report took the significant-but also unusual-position of trying to identify the underlying causes of problems in boys' schools rather than assuming that boys themselves or the system of separate schooling accounted for all of these problems. This one report thus anticipated some recent research successfully considering the multiplicity of complex factors that shape education in a single-sex school (Herr & Arms, 2004;Lee, 1998;Salomone, 2003;Woody, 2002). However, in the Soviet case, as in contemporary discourse, nuanced arguments about multifactor causation were overwhelmed by arguments attributing all of the advantages or all of the problems of separate schooling to the single factor of gender.…”
Section: Repudiation Of Single-sex Educationmentioning
confidence: 79%
“…The case study ultimately revealed that teachers in these schools responded to all three types of incentives; the fear of job loss was an exceptionally serious concern for just over one third of teachers. Herr and Arms (2004) examined the impact of teacher evaluation policy on a single-sex academy (SSA) by exploring how accountability measures affected the implementation of what was widely touted as being primarily a gender-based reform for students at one California middle school. The impact of high-stakes testing on curriculum and the roles of teachers was addressed as well as how the multiple, simultaneously implemented reforms derailed the possibilities inherent in the SSA.…”
Section: Review Of the Related Literature Teacher Evaluation Policymentioning
confidence: 99%